1992
DOI: 10.1055/s-2007-1010515
|View full text |Cite
|
Sign up to set email alerts
|

Self-Expanding Metal Stents for Palliation of Malignant Gastric Outlet Obstruction

Abstract: Treatment of inoperable gastric outlet obstruction caused by tumor compression is difficult and often unsatisfactory. The case of a 56-year-old female patient in whom self-expanding stents were implanted, successfully enabling oral nutrition, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 0 publications
0
32
0
2
Order By: Relevance
“…More recently, enteral SEMS have been used to palliate malignant gastric outlet stenosis and gastroduodenal obstructions after Truong et al [22] published their fi rst stent procedure in 1992. Today it is accepted that placement of a SEMS for gastric outlet obstruction has the potential of providing immediate and more durable relief than other non-surgical modalities [12] .…”
Section: Stentingmentioning
confidence: 99%
“…More recently, enteral SEMS have been used to palliate malignant gastric outlet stenosis and gastroduodenal obstructions after Truong et al [22] published their fi rst stent procedure in 1992. Today it is accepted that placement of a SEMS for gastric outlet obstruction has the potential of providing immediate and more durable relief than other non-surgical modalities [12] .…”
Section: Stentingmentioning
confidence: 99%
“…Radiologists were the first to offer an alternative to surgery by demonstrating the feasibility of stent placement using a peroral or percutaneous approach under fluoroscopic guidance [35] , but this approach never gained popularity due to its invasiveness and limited success rate [4] . Technological advances have led to the development of selfexpandable metallic stents that can pass through the operating channel of a therapeutic endoscope, allowing for endoscopic placement with fluoroscopic guidance, first described by Truong et al [6] in 1992. Endoscopic treatment has become more successful as this approach has increased in popularity.…”
Section: Introductionmentioning
confidence: 99%
“…Truong and collegues (Truong et al, 1992) also reported palliative treatment of malignant gastric outlet obstruction using a self-expanding metal stent.…”
Section: Recurrent Bulbar Urethral Stricturesmentioning
confidence: 99%